Exergy-based Investigation of Various Heat Pumps for Enhancement of Their Thermodynamic Efficiency - Voloshchuk, Volodymyr; Gullo, Paride (Моделювання, керування та інформаційні технології, 2019)
The work demonstrates the results of application of the detailed advanced exergetic analysis to air-source, watersource and wastewater-source heat pumps providing space heating in the built environment. Cumulative values based on seasonal exergy destruction are used for deriving conclusions. It is shown that in the specified conditions of the investigated systems priorities for improving should be given to heat exchangers.